"Everything Always Works": Continuity as a Source of Disaster Preparedness Problems. Issue 3 (November 2014) - Baker, Natalie D.
This paper offers new theoretical explanations about the problems with disaster preparedness efforts for vulnerable publics. Findings were developed through an inductive, grounded theory study conducted among staff and students at a large university in Southern California. Disaster preparedness is traditionally conceptualized as a collection of practices consisting of the collection and storage of material objects, resources, knowledge, and plans. People who do not engage in these activities in known risk areas are often blamed for the negative consequences of disaster. Here it is argued that preparedness reflects an assumed continuity between pre-and post-disaster contexts. This is closely tied to the pervasive need for social actors to maintain a sense of continuity in everyday life otherwise known as ontological security. The continuity of infrastructure and everyday life are major obstacles to the engagement of preparedness efforts for people. This study shows the notion of a potential catastrophe presents as an ontological crisis that impedes people's preparedness practices on both organizational and individual levels. It also demonstrates how the very idea of preparedness as directly connected to successful response is a product of the particular societal context of a risk area.